(untitled) (Journal of Laboratory Animal Science, 2024)
A spontaneous genetic mutation in Sprague Dawley rats was detected at the ICMR-NIN animal facility. The spontaneously mutated rat was examined for body composition, serum biochemistry, peripheral blood CD4 and CD8 cell population, and spontaneous tumour growth. We observed the spontaneous development of tumours in 24 animals on crossbreeding. The animals showed no significant differences in vital organ structure as compared to the heterozygous animals. Interestingly, both homozygous (hairless) and heterozygous rats developed spontaneous fibroadenomas in their mammary glands during adulthood, which was distinct from the parent NIN/SD rat colony. Importantly, there was no connection between the biochemical and T cell population and the presence of these tumours. The histological characteristics of the tumours closely resembled mammary tumours in humans. In conclusion, the hairless SD rat model with thymus will serve as a valuable tool in cancer research, particularly in mammary tumour studies.